Power Discourse: Analysis of Zulfikar Ghose Collection of Poems in perspective of Michel Foucault’s Bio Power Theory - Fiaz, Maryam; Rafique, Hina; Tabasum, Farhana (International Journal of English Literature and Social Sciences (IJELS), 2019)
The present research study is an analysis of Zulfikar Ghose’ poetry who is Pakistani poet writing in English. The researcher aims at analyzing his collection of poetry 50 Poems: Selected and New Poems in the light of Michael Foucault’s Biopower theory. Ghose’ collections of poetry are embedded with the elements of Diaspora, exile, alienation, loneliness, strangeness and search as well as quest for his own identity and cultural values. The study has investigated the language phenomenon of his poems under the framework of Foucault’s theory. Hence, few of the poems from the collection have been analyzed from the perspective of notion of power and biopower to argue the notion that Ghose poetry talks about power and negotiates power ideology. The colonial burden of the subjects in his poetry, the cultural erosion and identity crisis and supremacy of language has been pointed out under the canopy of power matrix. The study positively contributed to Pakistani literature and modern literary theory.